The Othering Bollywood: Nobleness and Savagery in Khuda Gawah and Dharmatma - Marjuque Ul Haque (Asiatic: IIUM Journal of English Language and Literature, 2023)
Afghanistan, popularly known as the graveyard of empires, has long been a contested site in geopolitics. With the Taliban coming to power after its victory over the US, it has become more critical than ever to discuss how Afghanistan has been presented in the media. While Hollywood’s long history of Orientalist gaze particularly towards Muslim nations is apparent in its vilified representation of Afghans in films like Iron Man (2008), Red Sands (2009), 12 Strong (2018), and The Outpost (2020), Bollywood’s representations of Afghanistan have not been studied with similar critical parameters. With Bollywood exerting significant influence as one of the largest film industries in the world, it has become imperative for us to learn whether Afghanistan has been subject to the same Orientalist gaze. This paper examines two pre-9/11 Bollywood films Khuda Gawah (1991) and Dharmatma (1975) in order to better understand this issue.